A risk factor model for peristomal skin complications - Anne Steen Hansen, Cecilie Jæger Leidesdorff Bechshøft, & Lina Martins, & Jane Fellows, & Birgitte Dissing Andersen, & Gillian Down, Tonny Karlsmark, & Gregor Jemec, & David Voegeli, & Zenia Størling and & Lene Feldskov Nielsen (WCET Journal - Portuguese Edition, 2022)
For people living with an ostomy, leakage and peristomal skin complications (PSC) are common issues that often appear together. Better means of preventing these issues could improve the quality of life of these patients. The purpose of the research presented here was to identify and build a model of risk factors for PSC. Risk factors were identified via discussion sessions with Coloplast’s internal ostomy care experts, the Coloplast Skin Expert Panel, the Global Coloplast Ostomy Forum (COF), and 18 national COF boards, collectively representing more than 400 ostomy care nurses from around the world. Risk factors were identified by these expert groups, analysed, clustered into categories, and discussed in several stages, resulting in the risk factor model for PSC, comprising three overall categories and their related risk factors (n=24). Consensus on the model was achieved using a modified Delphi process involving over 4000 experts within ostomy care from 35 countries. In parallel, a systematic literature review of risk factors for PSC was performed to identify primary literature supporting the model. Relevant articles published from 2000 until August 2020 were included in the review, and 58 articles were found to support 19 out of the total 24 risk factors. The risk factor model for PSC was ratified by the Coloplast Skin Expert Panel and the Global COF and holds potential to be included in guidelines for healthcare professionals and to be used as a tool in daily clinical practice.